Enhancing the Alphabet Recognition Skill by Using Educational Games (HAPCAB Model) of Primary 1 Students at Puyud Community School, Pattani Province, Thailand - Masae, Yamilah; Thesa, Khodiyo; Akhter, Bilkis; Baneng, Mariyae; Masoh, Khoyriyah (Manna wa Salwa Foundation (Yayasan Manna wa Salwa), 2024)
The purpose of this research was to investigate the effectiveness of using educational games, specifically the HAPCAB model, in improving students' alphabet recognition skills in primary 1 students at Puyud Community School in Pattani Province, Thailand. The study included 27 students in the first semester of 2022. The students were selected through purposive sampling. The research instruments involved lesson plans, pre-tests and post-tests for alphabet recognition, and a satisfaction measurement scale. The results of the research showed that students' alphabet recognition skills improved after using the HAPCAB model, with a higher achievement score of 11.85 compared to before. Additionally, the students had a very favorable level of satisfaction with the HAPCAB model, with a mean score of 4.70.